The boost for reading: Effects on classroom practices and student outcomes - Helena Holmlund; Josefin Häggblom; Erica Lindahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
We evaluate the "Boost for Reading", an in-service training program for teachers aimed at improving the teaching of literacy and boosting students' reading and writing proficiency. The program provides research summaries about teaching strategies as a basis for group-based discussion, lesson preparations and evaluations under the supervision of a coach. The program was rolled out across Swedish compulsory schools in school years 2015/16-2017/18. We analyze the effects of the intervention using a staggered difference-in-differences strategy excluding treated schools as controls. We find that in lower secondary school, the program shifted the teaching towards a stronger focus on "reading strategies" and raised student test scores in the Swedish language, social study subjects, and science studies by on average 2-5 percent of a standard deviation, respectively. However, we find no effects on teaching practices at stage 1, and accordingly, no effects on the youngest students' test scores.
Keywords: I20; I28; 330; teacher training; professional development; literacy